Baby Bear, Baby Bear, What do you See? - Oso Bebe, Oso Bebe, Que Ves Ahi? - Martin, Bill, 1916-2004.; Carle, Eric; Beguiristai?n, Luisa (New York : Henry Holt, 2020)
Baby Bear, Baby Bear, What Do You See? is the final collaboration from this bestselling author-illustrator team. Young readers will enjoy Baby Bears quest to find Mama, and theyll revel in identifying each of the native North American animals that appear along the way. The central focus on the special bond between Mama and baby makes a fitting finale to a beloved series.
Parallel text in English and Spanish.
Keywords: Bears -- Juvenile fiction; Mother and child -- Juvenile fiction; Bears -- Fiction; Mother and child -- Fiction; Spanish language materials -- Bilingual; Board books -- Juvenile fiction; Board books; Fiction; Juvenile works; Stories in rhyme